LINGUISTIC CHARACTERISTICS OF ENGLISH DICTIONARIES AND THEIR NEW TECHNOLOGIES OF COMPILING ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
The thesis deals with the linguistic peculiarities of dictionaries. The research highlights the peculiarities of the range and scope of dictionary material, the arrangement of dictionary and polysemous word meanings, information type of dictionary items and dictionary purposes.